PERKEMBANGAN TEKNOLOGI DAN KUALITAS PELAYANAN NASABAH PADA BAITUL MAAL WA TAMWIL LATANSA GONTOR - Annas Syams Rizal Fahmi; Tegar Cahyo Wibowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to determine the effect of technological developments on customer service at BMT Latansa Gontor. BMT Latansa Gontor is one of the financial institutions that runs its business activities always prioritizing the satisfaction of its customers, including serving people who want to apply for funding or save their assets. Various facilities have been offered by BMT Latansa Gontor to make it easier to carry out customer transactions. The services provided by BMT Latansa by following technological developments are not as sophisticated and as advanced as other Islamic Financial Institutions. But the best service to customers is the core of the application of current technological developments. Where most of the Latansa Gontor BMT customers have a background that is not too middle to upper so that the development of technology and services provided at this time can influence and improve services for Latansan Gontor BMT customers. Where the service makes it easier for their affairs and also increases the quality of service to BMT Latansa Gontor customers.